Analysis of the Reported Ethical Complaints and Violations to the Commission on Rehabilitation Counselor Certification, 2006–2013. (April 2015) - Hartley, Michael T.; Cartwright, Brenda Y.
This study reviewed ethical complaints and violations received from Fiscal Year 2006–2013 by the Commission on Rehabilitation Counselor Certification. There were 71 complaints, of which 37 cases (52.1%) progressed to full adjudication. Of the cases involving a violation, more than half (56.4%) involved ethical misconduct pertaining to role and relationship boundaries, client rights and welfare, and honest and responsible conduct. Strategies to ameliorate common violations as well as define and promote the ethical behavior of all Certified Rehabilitation Counselors are provided.